Lay persons in catechesis. Experience and challenges in the case of Slovenia - Tadej Stegu (Polonia Sacra)
Unlike in most other countries, religious education did not return to public schools in Slovenia after the fall of communism. The Catholic Church intensively introduced and developed catechesis in parishes. The new Slovenian Catechetical Plan opens the door to consider the various forms of catechesis already taking place in parish communities and to a lifelong model of catechesis that is not confined to the period of childhood and adolescence. The article analyses the development of the field of catechesis in Slovenia and the role of lay catechists. It highlights the main trends and challenges in catechesis and some of the existing solutions that no longer look only at the age of candidates but take into account their maturity and readiness when preparing to receive the sacraments of initiation. The analytical research is further illuminated by the author’s personal experience as a layperson involved in catechesis.